A 5-year comparison of marginal bone level following immediate loading of single-tooth implants placed in healed alveolar ridges and extraction sockets in the maxilla - Berberi, Antoine N.; Sabbagh, Joseph (Frontiers in Physiology, 2014)
Purpose: The aim of present investigation was to evaluate marginal bone level after 5-year follow-up of implants placed in healed ridges and fresh extraction sockets in maxilla with immediate loading protocol. Materials and Methods: Thirty-six patients in need of a single-tooth replacement in the anterior maxilla received 42 Astra Tech implants (Astra Tech Implant system™, Dentsply Implants, Mölndal, Sweden). Implants were placed either in healed ridges (group I) or immediately into fresh extraction sockets (group II). Implants were restored and placed into functional loading immediately by using a prefabricated abutment. Marginal bone level relative to the implant reference point was recorded at implant placement, crown cementation, 12, 36, and 60 months following loading using intra-oral radiographs. Measurements were made on the mesial and distal sides of each implant. Results: Overall, two implants were lost from the group II, before final crown cementation: they were excluded from the study. The mean change in marginal bone loss (MBL) after implant placement was 0.26 ± 0.161 mm for 1 year, and 0.26 ± 0.171 mm for 3 years, and 0.21 ± 0.185 mm for 5 years in extraction sockets and was 0.26 ± 0.176 mm for 1 year and 0.21 ± 0.175 mm for 3 years, and 0.19 ± 0.172 mm for 5 years in healed ridges group. Significant reduction of marginal bone was more pronounced in implants inserted in healed ridges (P < 0.041) compared to fresh surgical extraction sockets (P < 0.540). Significant MBL was observed on the mesial side of the implant after cementation of the provisional (P < 0.007) and after 12 months (P < 0.034) compared to the distal side which remained stable for 3 and 5 years observation period. Conclusions: Within the limitations of this study, responses of local bone to immediately loaded implants placed either in extraction sockets or healed ridges were similar. Functional loading technique by using prefabricated abutment placed during the surgery time seems to maintain marginal bone around implant in both healed and fresh extraction sites.